Canopy morphological changes and water use efficiency in winter wheat under different irrigation treatments - Hong-xiang ZHAO; Ping ZHANG; Yuan-yuan WANG; Tang-yuan NING; Cai-long XU; Pu WANG (Journal of Integrative Agriculture, 2020)
Water is a key limiting factor in agriculture. Water resource shortages have become a serious threat to global food security. The development of water-saving irrigation techniques based on crop requirements is an important strategy to resolve water scarcity in arid and semi-arid regions. In this study, field experiments with winter wheat were performed at Wuqiao Experiment Station, China Agricultural University in two growing seasons in 2013–2015 to help develop such techniques. Three irrigation treatments were tested: no-irrigation (i.e., no water applied after sowing), limited-irrigation (i.e., 60 mm of water applied at jointing), and sufficient-irrigation (i.e., a total of 180 mm of water applied with 60 mm at turning green, jointing and anthesis stages, respectively). Leaf area index (LAI), light transmittance (LT), leaf angle (LA), transpiration rate (Tr), specific leaf weight, water use efficiency (WUE), and grain yield of winter wheat were measured. The highest WUE of wheat in the irrigated treatments was found under limited-irrigation and grain yield was only reduced by a small amount in this treatment compared to the sufficient irrigation treatment. The LAI and LA of wheat plants was lower under limited irrigation than sufficient irrigation, but canopy LT was greater. Moreover, the specific leaf weight of winter wheat was significantly lower under sufficient than limited irrigation conditions, while the leaf Tr was significantly higher. Correlation analysis showed that the increased LAI was associated with an increase in the leaf Tr, but the specific leaf weight had the opposite relationship with transpiration. Optimum WUE occurred over a reasonable range in leaf Tr. In conclusion, reduced irrigation can optimize wheat canopies and regulate water consumption, with only small reductions in final yield, ultimately leading to higher wheat WUE and water saving in arid and semi-arid regions.